Unnatural (2018), volume 1 ebook Awakening. - Andolfo, Mirka (Unnatural (2018), 2018)
Leslie J. Blair is a simple pig girl. She loves sushi, and she hates her job. Her world is dominated by a totalitarian government that interferes in the personal lives of its citizens, punishing transgressors for so-called "unnatural"? relationships. Leslie dreams of something different for herself, but these dreams are becoming dangerous. And, when she wakes up, she thinks she's being watched"_ The hit Italian comic, an erotic fantasy/romantic suspense series by MIRKA ANDOLFO (Wonder Woman, Harley Quinn, DC Comics Bombshells), will take you to a colorful but terrible world full of anthropomorphic creatures"Óbut light on personal freedoms. Collects UNNATURAL #1-4. Author: Mirka Andolfo. Illustrator: Mirka Andolfo . 2018 Mirka Andolfo.